Controlled Release of TGF-β3 for Effective Local Endogenous Repair in IDD Using Rat Model - Zhu L; Yang Y; Yan Z; Zeng J; Weng F; Shi Y; Shen P; Liu L; Yang H (International Journal of Nanomedicine, 2022)
Lifan Zhu,1,2,* Yanjun Yang,1,* Zhanjun Yan,1,* Jincai Zeng,1 Fengbiao Weng,1 Yuhui Shi,1 Pengcheng Shen,1 Ling Liu,2 Huilin Yang2 1Department of Orthopedics, Suzhou Ninth Hospital Affiliated to Soochow University, Suzhou, 215200, People’s Republic of China; 2Department of Orthopedics, The First Affiliated Hospital of Soochow University, Suzhou, 215200, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huilin Yang, Department of Orthopedics, The First Affiliated Hospital of Soochow University, 188 Shizi Street, Suzhou, 215006, People’s Republic of China, Email suzhouspine@163.com Lifan Zhu, Department of Orthopedics, Suzhou Ninth Hospital affiliated to Soochow University, Suzhou, 215200, People’s Republic of China, Email zhulifan201608@163.comIntroduction: Intervertebral disc (IVD) degeneration (IDD) is one of the most widespread musculoskeletal diseases worldwide and remains an intractable clinical challenge. Currently, regenerative strategies based on biomaterials and biological factors to facilitate IVD repair have been widely explored. However, the harsh microenvironment, such as increased ROS and acidity, of the degenerative region impedes the efficiency of IVD repair. Here, an intelligent biodegradable nanoplatform using hollow manganese dioxide (H-MnO2) was developed to modulate the degenerative microenvironment and release transforming growth factor beta-3 (TGF-β 3), which may achieve good long-term therapeutic effects on needle puncture-induced IDD.Methods: Surface morphology and elemental analysis of the MnO2 nanoparticles (NPs) were performed by transmission electron microscopy and an energy-dispersive X-ray spectroscopy detector system, respectively. The biological effects of MnO2 loaded with TGF-β 3 (TGF-β 3/MnO2) on nucleus pulposus cells (NPCs) were assessed via cytoskeleton staining, EdU staining, qPCR and immunofluorescence. The efficacy of TGF-β 3/MnO2 on needle puncture-induced IDD was further examined using MRI and histopathological and immunohistochemical staining.Results: The MnO2 NPs had a spherical morphology and hollow structure that dissociated in the setting of a low pH and H2O2 to release loaded TGF-β 3 molecules. In the oxidative stress environment, TGF-β 3/MnO2 was superior to TGF-β 3 and MnO2 NPs in the suppression of H2O2-induced matrix degradation, ROS, and apoptosis in NPCs. When injected into the IVDs of a rat IDD model, TGF-β 3/MnO2 was able to prevent the degeneration and promote self-regeneration.Conclusion: Use of an MnO2 nanoplatform for biological factors release to regulate the IDD microenvironment and promote endogenous repair may be an effective approach for treating IDD.Graphical Abstract: Keywords: intervertebral disc degeneration, hollow manganese dioxide, transforming growth factor beta-3, oxidative stress, endogenous repair